2014
DOI: 10.1371/journal.pone.0106235
|View full text |Cite
|
Sign up to set email alerts
|

P2Y6 Receptor-Mediated Proinflammatory Signaling in Human Bronchial Epithelia

Abstract: P2Y receptors are expressed in virtually all epithelia and are responsible for the control of fluid and electrolyte transport. In asthmatic inflammation, the bronchial epithelia are damaged by eosinophil-derived, highly toxic cationic proteins, such as major basic protein (MBP). Consequently, extracellular nucleotides are released into the extracellular space from airway epithelial cells, and act in an autocrine or paracrine fashion to regulate immune functions. Our data show damage to the human bronchial epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
5
32
0
Order By: Relevance
“…FRET imaging experiments were performed using the MetaFluor Imaging System with FRET module (Molecular Devices, Downingtown, PA, USA) as described previously [24,25]. In brief, 16HBE14o- cells were transfected with the Epac-based cAMP sensor with Lipofectamine 2000 according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…FRET imaging experiments were performed using the MetaFluor Imaging System with FRET module (Molecular Devices, Downingtown, PA, USA) as described previously [24,25]. In brief, 16HBE14o- cells were transfected with the Epac-based cAMP sensor with Lipofectamine 2000 according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Primary human bronchial epithelial (HBE) cells were obtained from ScienCell Research Laboratories (Carlsbad, CA, USA) and maintained in Bronchial Epithelial Cell Medium (ScienCell Research Laboratories, USA) as described previously [7,10]. To simultaneously measure intracellular calcium concentration ([Ca…”
Section: Cell Culturementioning
confidence: 99%
“…Previously, we reported that bronchial epithelial damage due to poly-L-arginine (PLA), a surrogate that mimics the effects of eosinophil-derived major basic protein, causes the release of nucleotides and the subsequent activation of p38 and ERK1/2 mitogen-activated protein kinase (MAPK) and NF-κB signalling [7]. The pro-inflammatory cytokines IL-6 and IL-8 are released towards the apical compartment following the exposure of airway epithelial cells to PLA [8].…”
mentioning
confidence: 99%
“…16HBE14o- cells were maintained in Minimum Essential Medium with Earle’s salt supplemented with 10% (vol/vol) fetal bovine serum, 1% (vol/vol) L-glutamine, 100 IU/ml penicillin, and 100 µg/ml streptomycin, as previously described [23]. Cells were cultured in plastic flasks coated with fibronectin and collagen (BD Biosciences, San Jose, CA, USA) and were incubated in humidified 5% CO 2 air at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…These cells represent a good model for investigating transepithelial Cl - secretion [18, 19], airway inflammation, and airway remodeling [20-22]. Our previous studies showed that activation of P2Y receptors regulated epithelial Cl - secretion via both Ca 2+ - and cAMP-dependent pathways [23] and activated the PLC- D-myo-inositol 1, 4,5-triphosphate (IP 3 )-Ca 2+ signaling cascade in 16HBE14o- cells, which is also responsible for the secretion of at least two pro-inflammatory cytokines, interleukin (IL)-6 and IL-8, when the cells were challenged by cationic proteins [24]. Therefore, we sought to test whether CO would modulate the P2Y receptor-mediated calcium-signaling pathway.…”
Section: Introductionmentioning
confidence: 99%